Manipulating Fabric Quilting pada Kemeja: Ditinjau dari Deskripsi Perspektif Men’s Wear Fashion Trend - Kartika Sari, Almassda Rizky; Suhartini, Ratna (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Fashion plays an important role in shaping one's self-expression and identity. The development of male fashion is still less developed than female fashion because the addition of ornaments to men's fashion is often considered unmasculine and weak. The same goes for the way a man is dressed, who on average uses a shirt in everyday life like a work uniform or a service. The purpose of the purchase was to find out the outcome of a men's shirt with the addition of ornaments manipulating fabric quilting techniques to its fashion, which refers to the men's wear fashion trend. Using Japanese cotton fabric as the main ingredient. This research method uses a three-stage design process approach consisting of problem definition and research, creative exploration, and implementation. In the first phase, identify the initial problems of defining the ocean or ocean theme, pick up the source of fish ideas as well as sea waves, create a moodboard by looking for information about current men’s wear trends, and identify target markets. The second phase is that the researchers explore the idea by developing a fish quilting motif and creating six men's shirt designs along with the motif placement. One selected design will be realized into a men's shirt. The resulting shirt corresponds to the application of quilting techniques as decoration.